Sistem Manajemen Informasi Sebagai Pendukung Produksi di Industri Manufaktur (Studi Kasus : Perusahaan Penghasil Pensil) - Kurbandi Satpatmantyo B.R. (Teknik Informatika, Universitas Pelita Bangsa, 2021)
Data can be more than just raw materials information system . Data can be formed into an very valuable organizational resource. Organizations that lack of attention to data will be missed , therefore, the data should be organized and managed effectively with a good management information system , so as to give maximum benefit to the users in an organization included in a manufacturing company. Keywords : Management Information Systems , Manufacturing Companies